Emergencies in otolaryngology–head and neck surgery bootcamp: A novel canadian experience. (10th June 2014) - Chin, Christopher J.; Roth, Kathryn; Rotenberg, Brian W.; Fung, Kevin
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis A 1‐day intensive course (bootcamp) was developed, to teach junior otolaryngology–head and neck surgery (OTO–HNS) residents emergency procedural skills, clinical reasoning, and communication skills. This learning paradigm utilized a number of novel task trainers, panel discussions, and emergency simulations. The study objective was to assess the educational value of this bootcamp. Study Design Prospective cohort survey. Methods Residents were recruited from regional teaching centers within a 2000‐km radius of the simulation center. Preceptors fluent in English and in French were in attendance. Pre‐bootcamp outcome measures included the Kolb Learning Style Inventory and a self‐administered survey measuring confidence levels in performing specific OTO–HNS tasks. Post‐bootcamp outcome measures included a survey evaluating the bootcamp experience and a structured follow‐up telephone interview. Results Twenty‐eight residents participated in the bootcamp from across the United States and Canada. When asked if they felt that "overall, the educational day was an effective learning process, " the average score was 4.75/5.0. The vast majority of participants (92.9%) felt they would recommend the bootcamp to a future junior resident. Kolb learning styles that prefer active experimentation (acting, initiating, and deciding) were more common than those that utilize reflective observation (imagining, analyzing, reflecting), which favors a hands‐on model of learning. Conclusion This first Canadian OTO–HNS bootcamp demonstrated the feasibility and effectiveness of conducting a centralized bootcamp for regional training centers spanning multiple states/provinces and languages. Future bootcamps will be held annually and will ideally continue the natural evolution of surgical, hands‐on training. Level of Evidence N/A Laryngoscope 124:2275–2280, 2014